The Normalization of Preprints♦ - Drury, Luke (Journal of Information and Knowledge, 2022)
The last few years have seen an explosive growth in the use of preprints and the associated preprint servers by large sections of the scientific community. This article addresses the history of the preprint, its advantages, and potential disadvantages, and concludes with some recommendations for how the growing acceptance of preprint posting should be handled within academia and the changes in cultural norms (in other words its normalization) that this entails. (Garisto, 2019).